Asset pricing and the propagation of macroeconomic shocks - Ivan Jaccard (European Central Bank (ECB), 2018)
This paper considers the implications of habit formation and financial frictions for the propagation of macroeconomic shocks. In a model that is capable of matching asset pricing moments, a short-lived shock that destroys a small fraction of the economy's stock of pledgeable collateral generates a persistent recession, a stock market crash, and a flight-to-safety effect. This novel mechanism creates a tight link between the asset pricing implications of macroeconomic models and their ability to propagate and amplify the effects of macroeconomic shocks.
Keywords: E32; E44; G10; 330; Liquidity constraints; equity premium; Great Recession